Demystifying power, crime and social harm: the work and legacy of Steven Box - Scott, David; Sim, Joe (Critical criminological perspectives, 2023)
Introduction -- chapter 1: steven box: a ‘realist of a larger reality’(david scott and joe sim) -- part 1: corporate crime -- chapter 2: corporate crime, regulation and the stat (steve tombs) -- chapter 3. From corporate corruption to rentiership: extending box’s power, crime and mystification (steven bittle and jon frauley) -- chapter 4. Power, crime and deadly deception (david whyte) -- chapter 5. Climate change, planetary collapse and the ‘mystification’ of environmental crime (reece walters) -- chapter 6. Fighting for ‘justice for all’ in an era of deepening exploitation and ecological crisis (elizabeth bradshaw and paul leighton) -- part 2: power, state crime and social harm -- chapter 7. The neoliberal state: then and now (samantha fletcher and will mcgowan) -- chapter 8. The austerity state, ‘social junk’ and the mystification of violence (chris grover) -- chapter 9. Steven box and police crime: understanding and challenging police violence and corruption (will jackson) -- chapter 10. ‘the first narrative that is put out’: the mystification of police institutional violence (Lisa white and patrick williams) -- chapter 11. Immigration control, mystification and the carceral continuum (jon burnett) -- chapter 12. Criminal law categories as ideological constructs: the case of human trafficking (shahrzad fouladvand and tony ward) -- part 3: power, gender and sexual violence -- chapter 13. Power, sexual violence and mystification (kym atkinson and helen monk) -- chapter 14. ‘rape kills the soul’: the use of sexual violence by state and non-state actors in war and conflict (brenda fitzpatrick) -- chapter 15. Gender, powerlessness and criminalisation (kathryn chadwick and becky clarke) -- chapter 16. Mystification, violence and women’s homelessness (vickie cooper and dan mcculloch) -- part 4: demystifying social harm -- chapter 17. Standing on the shoulders of a criminological giant: steven box and the question of counter-colonial criminology (biko agozino) -- chapter 18. The policing of youthful ‘social dynamite’ within neo-liberal capitalism: continuities, discontinuities and alternatives (jodie hodgson) -- chapter 19. Demystifying injustice: joint enterprise law and miscarriages of justice (janet cunliffe and gloria morrison) -- chapter 20: punishment in ‘this hard land’: conceptualising the prison in power, crime and mystification (joe sim) -- chapter 21. Demystifying murder: open university pedagogy, social murder, and the legacy of steven box (deborah h. Drake and david scott).